2017
DOI: 10.1186/s12864-017-4251-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of a lowly virulent strain of Erwinia amylovora in shoots of two apple cultivars – susceptible and resistant to fire blight

Abstract: Background Erwinia amylovora is generally considered to be a homogeneous species in terms of phenotypic and genetic features. However, strains show variation in their virulence, particularly on hosts with different susceptibility to fire blight. We applied the RNA-seq technique to elucidate transcriptome-level changes of the lowly virulent E. amylovora 650 strain during infection of shoots of susceptible (Idared) and resistant (Free Redstar) apple cultivars.ResultsThe highest number of differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 82 publications
(100 reference statements)
2
25
0
Order By: Relevance
“…When analysing flhF and iroN2, it was found that flhF, a flagellar biosynthesis pathway gene, was highly up-regulated, while iroN2, which encodes the TonB-dependent receptor, was down-regulated in planta. The results of the reference gyrB, ffh and pykA genes in terms of the relative gene expression analysis agree with the results obtained in preliminary analysis of the expression of flhF and iroN2 in transcriptomes obtained after RNA-seq [48]. GyrA did not make significant changes in the results obtained (data not shown).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…When analysing flhF and iroN2, it was found that flhF, a flagellar biosynthesis pathway gene, was highly up-regulated, while iroN2, which encodes the TonB-dependent receptor, was down-regulated in planta. The results of the reference gyrB, ffh and pykA genes in terms of the relative gene expression analysis agree with the results obtained in preliminary analysis of the expression of flhF and iroN2 in transcriptomes obtained after RNA-seq [48]. GyrA did not make significant changes in the results obtained (data not shown).…”
supporting
confidence: 88%
“…The flhF gene was up-regulated by 231.64-fold (SE 42.01) compared with that of a pure bacterial culture; however, for the iroN2 gene, the opposite result was noted i.e., down-regulation in planta (− 16.2-fold; SE 2.072) compared to pure bacterial culture. Compared to the results of transcriptome analysis by RNA seq, the expression values of the flhF and iroN2 genes obtained in this study were similar [48].…”
Section: Expression Analysis Of the Flhf And Iron2supporting
confidence: 78%
“…Two main classes of motility reported in E. amylovora include flagellar motility (Raymundo and Ries, ) and twitching motility through type IV pili (Berry et al ., ). Flagellar motility provides a means whereby the E. amylovora cells can swim through flower nectar to reach host tissues, and it has been suggested that flagella play an important role in virulence (Holtappels et al ., ; Puławska et al ., ). Like other members of the Enterobacteriaceae family, E. amylovora bears peritrichous flagella.…”
Section: Introductionmentioning
confidence: 97%
“…Novel minor resistance alleles from domesticated apples can require less time and fewer cycles of backcrossing to develop breeding lines with improved fire blight resistance. Furthermore, highthroughput RNA-sequencing (RNA-Seq) have been used to characterize molecular mechanisms related to fire blight infection in apple cultivars 'Golden Delicious', 'Idared' and 'Free Redstar' 32,33 . RNA-Seq was used to identify transcriptome level changes in flowers of 'Golden Delicious' challenged with E. amylovora strain CFBP 1430 32 .…”
Section: Introductionmentioning
confidence: 99%